Anterior dental microwear textures show habitat-driven variability in Neandertal behavior. Issue 105 (April 2017) - Krueger, Kristin L.; Ungar, Peter S.; Guatelli-Steinberg, Debbie; Hublin, Jean-Jacques; Pérez-Pérez, Alejandro; Trinkaus, Erik; Willman, John C.
Abstract: The causes of Neandertal anterior tooth wear patterns, including labial rounding, labial scratches, and differential anterior-posterior wear, have been debated for decades. The most common explanation is the "stuff-and-cut" hypothesis, which describes Neandertals clamping down on a piece of meat and slicing a portion close to their lips. "Stuff-and-cut" has been accepted as a general aspect of Neandertal behavior without fully assessing its variability. This study analyzes anterior dental microwear textures across habitats, locations, and time intervals to discern possible variation in Neandertal anterior tooth-use behavior. Forty-five Neandertals from 24 sites were analyzed, represented by high-resolution replicas of permanent anterior teeth. The labial surface was scanned for antemortem microwear using a white-light confocal profiler. The resultant 3D-point clouds, representing 204 × 276 μm for each specimen, were uploaded into SSFA software packages for texture characterization. Statistical analyses, including MANOVAs, ANOVAs, and pairwise comparisons, were completed on ranked microwear data. Neandertal descriptive statistics were also compared to 10 bioarchaeological samples of known or inferred dietary and behavioral regimes. The Neandertal sample varied significantly by habitat, suggesting this factor was a principal driving force for differences in Neandertal anterior tooth-use behaviors. The Neandertals from open habitats showed significantly lower anisotropy and higher textural fill volume than those inhabiting more closed, forested environments. The texture signature from the open-habitat Neandertals was most similar to that of the Ipiutak and Nunavut, who used their anterior teeth for intense clamping and grasping behaviors related to hide preparation. Those in more closed habitats were most similar to the Arikara, who did not participate in non-dietary behaviors. These Neandertal individuals had a broad range of texture values consistent with non-dietary and dietary behaviors, suggesting they varied more in anterior tooth-use behaviors and exploited a wider variety of plant and animal resources than did those from open habitats.